Surveilans Penderita Talasemia di RSUP Dr. Sardjito Yogyakarta Tahun 2004 - Rosita, Linda (Universitas Muhammadiyah Yogyakarta, 2007)
Surveillance based on demography data and laboratory data of patient ’s Thalassemia needing routine blood transfusion give a contribution in managing the disease in society and increase the service to patient and its family. The aim of this study is to investigate the epidemiology clinical and laboratory aspect of the Thalassemia patient needing routine transfusion in RSUP Dr. Sardjito Yogyakarta. The study retrospectively, subject are the patient with routine transfusion and have complete laboratory data. Data are taken from patient’s Thalassemia needed routine transfusion or suspect Thalassemia and other variables needed rutinized from their medical records during of2004. There are 29 subject this study 18% is major Thalassemia, age 1-14 year, needing blood transfusion for a lifetime (48%), living outside DIY (52%) that is Central Java of part of south Pacitan. Family History knew (86%) at patient ’s, peripheral blood smear supporting diagnosed by Thalassemia (86%), existence of splenomegaly most of allpatient’s, test fragilities osmotic (71%) supporting diagnosed Thalassemia. Haemoglobin Rate gyrate 2,7-10g%, there are make-up of amount retikulosit till 4,9%,. pattern of Electrophoresis Hb there are improvement Hb S/D/G till 70mg%, improvement of Hb A2 till 86,7mg%, and also the existence of improvement of Hb F of father 2,84% and improvement of Hb F of mother 1,26%. Peripheral blood smear a step aside and usable osmotic fragility test as screening Thalassemia after existence of later clinic suspicion can be continued test of electrophoresis Hb and analyze the fi gene DNA. Test Electrophoresis Hb require to be socialized to doctor to make diagnosed by Thalassemia and suspicion to traits Thalassemia.Surveilans yang berbasis data demografi dan laboratorium pada pasien Talasemia yang memerlukan transfusi darah rutin dapat memberikan kontribusi terhadap penaggulangan penyakit di masyarakat dan meningkatkan mutu pelayanan kepada pasien dan keluarganya. Penelitian secara retrospektif observasional, subyek penelitian pasien Talasemia menjalani transfusi rutin atau pasien dicurigai klinis Talasemia, memiliki data demografi dan data laboratorium lengkap, dirawat di Instalasi Kesehatan Anak (InsKA) dan Unit Penyakit Dalam (UPD) RSUP Dr. Sardjito. Kriteria eksklusi jika sampai akhir perawatan diagnosis Talasemia belum dapat ditegakkaan Terdapat 29 subyek penelitian dengan Talasemia mayor (18%), kelompok umur terbanyak 1-14 tahun, memerlukan transfusi darah seumur hidup (48%), berdomisili di luar DIY (52%) yaitu Jawa tengah bagian selatan hingga Pacitan. Riwayat keluarga pada pasien diketahui (86%), morfologi darah tepi yang mendukung diagnosis Talasemia (86%), adanya splenomegali pada hampir semua pasien, tes fragilitas osmotik (71%) mendukung diagnosis Talasemia. Kadar hemoglobin berkisar 2,7-10g%, peningkatan jumlah retikulosit hingga 4,9%. Pola elektroforesis Hb terdapat peningkatan pada Hb S/D/G hingga 70mg%, peningkatan Hb A hingga 86,7mg%, adanya peningkatan Hb F ayah rata-rata 2,84% dan peningkatan Hb F ibu rata-rata 1,26%. Morfologi darah tepi dan tes fragilitas osmotik dapat dipakai sebagai skrining Talasemia setelah adanya kecurigaan klinis dilanjutkan pemeriksaan elektroforesis Hb dan analisis DNA gen B. Pemeriksaan elektroforesis Hb perlu disosialisasikan kepada klinisi untuk menegakkan diagnosis Talasemia dan kecurigaan terhadap traits Talasemia.